Compact SIW Based Planar Inverted F Antenna - Annalakshmi, T; Ramesh, S (International Journal of Engineering and Technology, 2018)
This article describes the single band Planar Inverted F Antenna (PIFA) for movable application. This structure of the antenna comprises of a rectangular patch located on top of the Flame Retardant 4 (FR4) dielectric substrate using Substrate Integrated Waveguide (SIW).The bottom side of the substrate is completely covered by a full ground made up of copper material. The complete measurement of PIFA is 21.72 mm x 18.5 mm x 4mm.This antenna has low profile, small size, and good gain hence it is more suitable for mounting on the cellular phone. The performance of PIFA antenna is represented in terms of return loss, VSWR and gain by using the simulation tool Ansys HFSS.Â Â